Parametric analysis of the implementation of energy efficiency measures and their impact on the energy efficiency class of the building - Deshko, V.; Bilous, I.; Yeromenko, V.; Boiko, T.; Shevchenko, O. (Energy and Automation, 2024)
Improving the energy efficiency of buildings is an important component on the way to energy efficiency of the country as a whole. The article investigates the impact of implementing various combinations of energy saving measures and their impact on the energy efficiency class of buildings, using the example of the educational building of the Igor Sikorsky Kyiv Polytechnic Institute (Kyiv). The existing state of the building corresponds to the energy efficiency class "G".A complete thermal modernization of the building in accordance with the current requirements for thermal protection can reduce energy consumption by the building by up to 44 % and reaches the energy efficiency class "E". It was found that the introduction of intermittent heating modes can save 12 % for an un-insulated building and 7 % for an insulated building. Heat recovery in ventilation systems can save 23 % and 48 % of energy for non-insulated and insulated buildings, respectively. Implementation of a comprehensive thermal modernization of the building envelope in combination with heat recovery in ventilation systems in combination with intermittent operating modes allows to move to energy efficiency class "B". When replacing heat supply sources after a complete thermal modernization of a building, it can move to energy efficiency class "A" when using heat pumps.Kay words: energy consumption, energy need, heat transfer, certificate, energy efficiency class